Liquid Biopsies in Solid Tumors - Cristofanilli, Massimo; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Humana Press, 2017)
This volume, with chapters written by experts in the field of cancerous tumors, details the key factors associated with liquid biopsies in solid tumors: blood-based diagnostics; circulating tumor cells; enumeration and molecular analysis (association with breast cancer); epithelialmesenchymal transition; detection and monitoring; circulating-free tumor DNA; CTCs and ctDNA; and the exosome. The field of blood-based diagnostics is rapidly evolving demonstrating the possibility of real-time molecular analysis of cancer cells and their phenotype and genotype. Circulating Tumor Cell (CTCs) have demonstrated prognostic and predictive value in advanced cancer and represents a source of tumor cells for transcriptome and genomic analysis. Most recently, the detection of genomic abnormalities in the peripheral blood by sensitive and selective PCR methods (liquid biopsy) opened to the option of a comprehensive blood-based tumor analysis. Similar information can be obtained by analysis of exosome, a natural packaging and messaging system being explored in advanced malignancies. The final frontier is the evaluation of immune cells determinant of innate and adaptive immunity.
1.Blood-based diagnostics in solid tumors: an overview -- 2.Circulating tumor cells (CTCs) in primary disease: the seed for metastasis -- 3.Enumeration and molecular analysis of CTCs in metastatic disease: The breast cancer model -- 4.Epithelial-Mesenchymal Transition (EMT) and cancer stem cells (CSCs): The traveling metastasis -- 5.Detection and monitoring of circulating immune cells in solid tumors: shifting priorities -- 6.Circulating-free tumor DNA (ctDNA): the real-time liquid biopsy -- 7.CTCs and ctDNA: two tales of a complex biology -- 8.Exosome: decoding the messaging system.
Keywords: Medicine; Cancer research; Biomedicine; Cancer research